Zakat administration: an analysis of the past approach - Tahir, Ibrahim Nuhu; Oziev, Gapur (2018)
Zakāt is one of the five pillars of Islām and even though it is a system designed by Allāh the Almighty, it has faced many challenges across the centuries in its implementation. The main objectives of zakāt were well achieved during the early generations, from the time of the Prophet to the time of the Rightly Guided Caliphs. This success was a result of strict adherence to the text of Sharīʿah which is supposed to be understood literally in this matter. However, this is not the case in our contemporary era where mismanagement of zakāt occurs due to interference by those in authority and inappropriate ijtihad which have become obstacles that hinder achievement of the zakāt system objectives. The system is divinely revealed by Allāh and this is proof of its perfection and accuracy and thus needs no modification or change. The paper focuses on certain key issues of concern in managing the collection, preservation and distribution of zakāt. Unless these points are managed as prescribed by the Sharīʿah, the zakāt objectives cannot be achieved. JEL Classification: A0, A1, D3, D30